Neurotensin Receptor 1 Gene (NTSR1) Polymorphism Is Associated with Working Memory - Li, Jin; Chen, Chuansheng; Chen, Chunhui; He, Qinghua; Li, He; Li, Jun; Moyzis, Robert K.; Xue, Gui; Dong, Qi (PLOS ONE, 2011)
Background Recent molecular genetics studies showed significant associations between dopamine-related genes (including genes for dopamine receptors, transporters, and degradation) and working memory, but little is known about the role of genes for dopamine modulation, such as those related to neurotensin (NT), in working memory. A recent animal study has suggested that NT antagonist administration impaired working memory in a learning task. The current study examined associations between NT genes and working memory among humans. Methods Four hundred and sixty healthy undergraduate students were assessed with a 2-back working memory paradigm. 5 SNPs in the NTSR1 gene were genotyped. 5 ANOVA tests were conducted to examine whether and how working memory differed by NTSR1 genotype, with each SNP variant as the independent variable and the average accuracy on the working memory task as the dependent variable. Results ANOVA results suggested that two SNPs in the NTSR1 gene (rs4334545 and rs6090453) were significantly associated with working memory. These results survived corrections for multiple comparisons. Conclusions Our results demonstrated that NTSR1 SNP polymorphisms were significantly associated with variance in working memory performance among healthy adults. This result extended previous rodent studies showing that the NT deficiency impairs the working memory function. Future research should replicate our findings and extend to an examination of other dopamine modulators.